Arabic Language Program Management at Islamic Boarding School Nawaina of Islamic Junior High School 2 Malang - M Sholih Salimul Uqba; Agus Sulaiman; Meidias Abror Wicaksono; Ridwan; Faisal Mahmoud Adam Ibrahim (Mantiqu Tayr: Journal of Arabic Language, 2024)
The Arabic language is an essential part of Islamic education, as it is the language of the Quran and a key tool for understanding Islamic teachings. Many Islamic educational institutions offer specialized programs to teach the Arabic language to their students. Understanding the management processes involved in these Arabic language programs is important to ensure their effectiveness and continuous improvement. The aims of this study are to describe of the management of Arabic Language Program at Islamic Boarding School Nawaina Islamic Junior High School 2 Malang, with particular emphasis on the planning, organising, implementation and evaluation aspects. In this study, researchers employed a descriptive qualitative methodology. The data collection techniques are interviews and field observations which are then analyzed with 3 steps, namely data reduction, data presentation and conclusion drawing. The findings of this study indicate that in the planning management of the Islamic Boarding School Nawaina Arabic language program, a coordination meeting is held every semester between the head of the Islamic boarding school, teachers and santri assistants. As for the organizing stage, class classification of students and teachers is carried out. While at the implementation stage it is carried out in 3 Arabic language learning programs, including: Takhossus Kitab, Ta'lim Kitab, Muhadloroh and Compulsory Arabic Extracurricular. And at the evaluation stage, the assessment of student results is carried out through the final semester exam. Researchers propose that future research should prioritize investigating the impact of the Arabic language program on student learning outcomes and Islamic knowledge acquisition.